Substitutions in elite male field hockey - a case study - Linke, D.; Lames, M. (International Journal of Performance Analysis in Sport, 2016)
The purpose of this study was to (i) describe and analyse the substitution tactics of an international field hockey team during competitive match play and (ii) to identify the impact of bench periods on the physical output of players when re-entering active game play.